Identifikasi Dan Pengendalian Potensi Risiko Keselamatan dan Kesehatan Kerja (K3) di Toko Minimarket - Priska Karina Nasution; Susilawati Susilawati (PT. Alahyan Publisher Sukabumi, 2024)
In today's modern era, the growth of modern stores such as Indomaret, Alfamart, and so on is very rapid in all regions in Indonesia. Modern stores such as Indomaret and Alfamart can almost be found in every region and certain areas are even squeezed together between companies that turn their backs. This study aims to identify potential hazards and risks of work accidents in minimarket environments, focusing on Indomaret on Jl. Golf Course, Pancur Batu District, Deli Serdang Regency, North Sumatra. The research method used is qualitative descriptive through direct observation and documentation. The observations showed the potential for physical, ergonomic, biological, chemical, and psychosocial hazards in the minimarket. Physical hazards are associated with piles of products on the floor that can cause accidents, while ergonomic hazards occur due to lack of rest while working which can lead to muscle disorders. Biological hazards arise from the lack of protection against microorganisms, while chemical hazards are associated with the use of ovens and wires adjacent to microwaves. Psychosocial hazards are linked to stress due to financial problems. Risk control can be done through elimination, substitution, design, administration, and use of personal protective equipment. The concept of occupational safety and health (K3) is important to protect employees and customers. Hazard identification and risk control are important steps to prevent accidents and protect welfare in the convenience store environment.